A clinical and epidemiological study of hyperpigmentary disorder of face - Raikar, Dayanand; Javed, Mohammed Waseem; Takalkar, Anant Arunrao (International Journal of Research in Dermatology, 2020)
Background: Facial pigmentary disorders are a group of heterogenous entities, sharing a common clinical feature of altered pigmentation of the face and thus easily visible cosmetic disfigurement. Although the increased melanin provides protection from harmful effects of UV radiation, including photodamage and skin cancers, it also makes darkly pigmented skin more vulnerable to post-inflammatory dyspigmentation. The importance of these disorders is growing, as they form the major percentage of dermatology consultations. The objective of the study was to assess the clinical profile of patients with facial hyperpigmentation. Methods: The present cross-sectional hospital based observational study was conducted at Dermatology Department of during the period of June 2017 to December 2017 including patients with diagnosis of facial hyperpigmentation. Data analysed with SPSS 24 version. Results: 29% were from 21 to 30 years age group followed by 25% from 31 to 40 years age group. Mean age of the study population was 28.4±11.8 years. 76% were female patients. Commonly observed facial hyperpigmentation type was melasma in our study i.e. 46%. It is followed by post inflammatory hyperpigmentation (PIH) in 16% and ephilides in 8%. Rehl's melanosis and drug induced melanosis was seen in 7% each of the patients. Ephilides, Rehl's melanosis and drug induced was seen in 7% each of the patients. Family history of pigmentaory disorder was found in melasma, PIH and ephilides in our study. Conclusions: Commonly reported age group was 20-40 with female preponderance. Commonly observed facial hyperpigmentation type was melasma (46%), PIH (16%) and ephilides (8%).